Stocking rate and capital indicators in extensive sheep farms (sw spain) - Escribano Sánchez, Miguel; Rodríguez de Ledesma Vega, Antonio; Mesías Díaz, Francisco Javier; Pulido García, Francisco (Arch. Zootec, 2002)
The animal production systems in the SW of the Iberian Peninsula are characterized by extensive livestock farming. The data for the present study were collected by survey in the year 2000 from 96 dehesa sheep farms in Extremadura. We studied the stocking rate effects on a number of capital indicators for each farm. The data were analysed for three stocking rate levels: low (<0.25 UGM/ha), medium (0.25-0.5 UGM/ha), and high (0.5 UGM/ha). The differences were compared by analysis of variance, following the GLM procedure.
Keywords: Economic analysis; Extensive system; Sheep; Stocking rates

Stocking rate and capital indicators in extensive sheep farms (sw spain) - Escribano Sánchez, Miguel; Rodríguez de Ledesma Vega, Antonio; Mesías Díaz, Francisco Javier; Pulido García, Francisco (Arch. Zootec, 2002)
The animal production systems in the SW of the Iberian Peninsula are characterized by extensive livestock farming. The data for the present study were collected by survey in the year 2000 from 96 dehesa sheep farms in Extremadura. We studied the stocking rate effects on a number of capital indicators for each farm. The data were analysed for three stocking rate levels: low (<0.25 UGM/ha), medium (0.25-0.5 UGM/ha), and high (0.5 UGM/ha). The differences were compared by analysis of variance, following the GLM procedure.
Keywords: Economic analysis; Extensive system; Sheep; Stocking rates

Iberian ham - Sabio, E; Fallola, A; Sanabria, C; Vidal-Aragon, M C (BASIS OF THE QUALITY OF TYPICAL MEDITERRANEAN ANIMAL PRODUCTS, 1998)
Iberian dry-cured ham is a meat product elaborated from legs of Iberian pigs. This high quality product has been traditionally elaborated in Spain since ancient times. The production is centred in the Southwest of the Iberian Peninsula where it has a great economic, social, and ecological importance. Iberian dry-cured ham quality depends on the raw matter and the technology employed Raw matter quality depends on intrinsic factors (genotype, age, sex), extrinsic factors (feeding, habitat, management), and the slaughtering conditions. Respecting to genotype. at present it is frequent the employment of cross-breeding mainly with Duroc-Jersey (50% and 75% Iberian). The production system is extensive and has three different periods: preweaning, growing, and fattening, this last being fundamental from a quality viewpoint, establishing three commercial categories: `pienso', `recebo', and `bellota'. This production system causes seasoning in Iberian ham production. The elaboration process of Iberian dry-cured ham consists of four steps: salting, post-salting, drying, and cellar The long lasting of the process (18-24 months) and the high temperatures during the drying period (25-30 degrees C) are distinctive aspects of this technology. As compared to Parma or Serrano dry-cured hams, Iberian ham is characterised by: 1) low salt content, 2) high amount of intramuscular fat, rich in oleic acid, 3) high level of proteolysis and lipolysis, and 4) high amount of volatile compounds, mainly linear, medium-chain aldehydes and ketones. There are three Appellation of Origin: `Dehesa de Extremadura', `Guijuelo' and `Sierra de Huelva', and in the next future will appear `Valle de Pedroches'. The most important producer associations are AECERIBER, ACOREX, and ASICI. There are several research centres where this product is preferentially studied, standing out the Department of Agrofood technology of the Junta de Extremadura and the Veterinary faculty of the University of Extremadura.
Keywords: Extensive system; Iberian ham; raw matter